Global Agriculture: Vision and Approaches - Dastagiri, M.B. (European Scientific Journal, ESJ, 2017)
The perceived limits to producing food for a growing global population have been a source of debate and preoccupations for ages. Experts and the public alike seem to alternate between pessimism and optimism, anxiety and complacency, about the world food situation and outlook. Agriculture in the 21st century has multiple challenges. Globally, Agriculture it seems is back on the development agenda to meeting the Millennium Development Goals. The main objective of the paper is to analyse and trace insights of past and present of global agriculture and frame new vision of it. The status of global agriculture in general and continents and country-wise policies in particular from 61 countries of 6 continents were collected and insights are analyzed. These continent-wide policies can safeguard each country’s independence. New Vision for Agriculture calls for a new approach. The new approach of global leaders has aligned around the New Vision for Agriculture. Development of a “Road map for Achievement of the Vision is providing a framework for action and collaboration for global leaders. These includes exchanging ideas, collaborating with international scientists and agricultural institutions is part of the solution. The study found that agriculture must be global agenda in future and all countries should fix minimum support price policy must be world prices with 20% extra. The “double by 2050” analysis from the United Nations Food and Agriculture Organization revealed that food production in the developing countries would need to almost double The study found that developing countries have witnessed higher demands (2025) for wheat, maize, soybean, pig meat, poultry meat, sheep meat, beef and veal, whereas developed countries have witnessed higher demands for sugar. The globe has to develop a new strategy and global policies to meet the requirements of the rice. The future task of CGIAR&FAO must act as intelligent think tank on acquaint, analyse global research knowledge on future technologies, inventions, income models, latitude based science, space technologies, farm computer, Global Agricultural Growth and Policy coordination, climate financing, genetically modified crops on Mars, understanding too many variable effects on agriculture, digital agriculture, industrial farming, International Agricultural Education and transfer to capacity building of NARES System.